Galanin Receptors and Ligands - Webling, Kristin E.; Runesson, Johan; Bartfai, Tamas; Langel, Ülo (Frontiers in Endocrinology, 2012)
The neuropeptide galanin was first discovered 30 years ago. Today, the galanin family consists of galanin, galanin-like peptide (GALP), galanin–message associated peptide (GMAP) and alarin and this family has been shown to be involved in a wide variety of biological and pathological functions. The effect is mediated through three GPCR subtypes, GalR1-3. The limited number of specific ligands to the galanin receptor subtypes has hindered the understanding of the individual effects of each receptor subtype. This review aims to summarize the current data of the importance of the galanin receptor subtypes and receptor subtype specific agonists and antagonists and their involvement in different biological and pathological functions.